Open Distance Learning and the Management of Electoral Violence in Nigeria - OJO, Olusola Matthew (West African Journal of Open and Flexible Learning, 2017)
The phenomenon of internal conflict has arguably assumed an enduring image of the Nigerian society in its post-colonial epoch. Apparently, electoral violence has significantly compounded the problem as it manifests at the three stages of the electoral process, thereby undermining peace and security in the country. Despite existing studies on the generation, manifestation and consequences of electoral violence, the menace seems protracted and intractable by assuming various dimensions with the devastating implications for the democratic process and national integration. Using qualitative method of data collection, this study identifies inadequate democratic orientation as central among the variables determining the intensity of electoral violence in the country. Findings show that among other factors, the political elite take advantage of inadequate democratic education on the part of the masses to recruit youths as triggers of electoral violence. Hence, considering its flexibility, cost effectiveness and multiple modes, this study contends that ODL is a veritable medium of impacting democratic education in the citizenry with a view to preventing electoral violence and entrenching the democratic process in the interest of political stability and national integration. Résumé: Le phénomène des conflits internes a, sans doute, assumé une image durable de la société nigériane à l’époque postcoloniale. Apparemment, la violence électorale a considérablement aggravé le problème tel qu’il se manifeste aux trois étapes du processus électoral, compromettant ainsi la paix et la sécurité dans le pays. Malgré les études existantes sur la génération, la manifestation et les conséquences de la violence électorale, la menace semble prolongée et insoluble en prenant diverses dimensions avec des implications dévastatrices pour le processus démocratique et l’intégration nationale. En utilisant une méthode qualitative de collecte de données, cette étude identifie l’orientation démocratique inadéquate comme l’une des principales variables déterminant l’intensité de la violence électorale dans le pays. Les résultats montrent que l’élite politique, entre autres facteurs, profite d’une éducation démocratique inadéquate de la part des masses pour recruter des jeunes comme déclencheurs de la violence électorale. Par conséquent, compte tenu de sa souplesse, de son rapport coût-efficacité et de la multiplicité de ses modes de fonctionnement, la présente étude soutient que l’apprentissage ouvert et à distance est un véritable moyen d’influencer l’éducation démocratique des citoyens en vue de prévenir la violence électorale et d’enraciner le processus démocratique dans l’intérêt de la stabilité politique et de l’intégration nationale.